Establecimiento de un modelo para la gestión de microcréditos que permita minimizar los niveles de morosidad en las cooperativas de ahorro y crédito del Distrito Metropolitano de Quito parroquia Chillogallo. - Medina Martínez, Patricio Gonzalo (2015)
An expired credit creates additional costs for both the financial institution with a cumbersome collection management or portfolio sales, and customers due to increased collection costs and interest for late payment which are legal and regulated by the different entities of control but excessive for a client. No person acquires a loan in order to not pay the debt, on the contrary, this problem occurs for a number of reasons beyond their control which mostly ends up affecting your credit history and the chance to make a new credit. This thesis was conducted after having determined the need to present a management model as an alternative that would reduce default rates produced by the non-payment of claims in the parish of Chillogallo Metropolitan District of Quito and avoid any inconvenience and additional costs for both the bank and the customer. Were analyzed the different factors and variables economic partner that can directly or indirectly affect the functionality and purpose of the management model that aims to reduce the default rate produced by the non-paying customers, well, analysis of different indicators was performed financial financial institution in order to allow us to know the status and solvency of credit unions. Additional, after analysis, is determined to be necessary control, monitoring and credit advice post it will allow all values given to a customer, whether for its intended purpose and not diverted to other purposes. So it is also necessary that financial institutions give to their customers the facility to make payments on the loans granted by collecting societies, transfers, etc.